DD-019 Impact of incomplete prescriptions on patient waiting time in clinical trials. (14th February 2016) - Molina, A; Vicente, N; Palomar, C; Pueyo, C; Cuesta, I; Bermejo, T
Abstract : Background: Dispensing of investigational drugs is a more complex and longer process than dispensing commercial medications. Therefore, a correct prescription is essential to minimise the waiting time for patients. Purpose: To measure the delay in dispensing investigational drugs (ID) caused by an incomplete medication prescription (IMP). Material and methods: A prospective, observational, descriptive study was carried out in the pharmacy clinical trials department of a general hospital. All IMPs were recorded and the delay in dispensing was measured during March 2015. The ID dispensing process starts when the investigator requests the ID through the ID request (IDR). After that, the prescription is validated and dispensed by the pharmacist. A correct IDR should contain the protocol's name, investigator's signature, patient code, order date and drug designation. If one of these fields was missing, it was considered an IMP. For every IDR the pharmacist registered the following: the time when the prescription was handed in, mistakes identified and dispensing time. All IDR incidents were reported to the investigator and resolved before dispensing them. The average dispensing time for a correct prescription was compared against the average dispensing time of an IMP, in order to measure the delay in dispensing an ID. Results: 301 IDRs were analysed. The highest number of IDRs were from the oncology and haematology departments (54.1% (n = 163) vs 26.2% (n = 79)). 35 IMPs (11.6%) were detected: 20 (6.6%) from the haematology department, 9 (3.3%) from the oncology department and six from other departments. On average, the dispensing process time for a correct IDR was 5.8 ± 5.1 min compared with 16.0 ± 11.0 min to dispense an ID with an IMP. The average delay in the dispensing process was 10.2 min. The difference was found to be statistically significant (p < 0.05). Conclusion: The majority of IMPs were found from the haematology and oncology departments, both departments having the highest number of IDRs. IMPs increase dispensing time and can even triple patient waiting time. No conflict of interest.